Food Handlers Personal Hygiene in The Cafeteria of SDN Model and its impacts on Total Plate Count (TPC) in Food - Upi - Almasari; Corie Indria Prasasti (JURNAL KESEHATAN LINGKUNGAN, 2019)
Canteen has an important role to provide of nutritious and safe food for students during school hours with relatively affordable prices. The results of Food and Drugs Monitoring (BPOM) inspection in 2013 by taking a sample of School Children Confectionary (PJAS) found that 80,79% of the samples confirmed as free from microbiological contamination. These results decrease in 2014, whereas PJAS samples confirmed as free from microbiological contamination was 76,18%. This study aimed to analyze the implementation of personal hygiene food handlers in the cafeteria of SDN Model to figures Total Plate Count (TPC) in food. This was a descriptive study using cross sectional design. Samples were taken with total sampling where the sample size in this study was the total population of cafeteria booth at SDN Model, there are 5 booths canteen, 5 food handlers, and 5 food samples were taken from each canteen booth. All food samples were tested for bacteriological quality using Total Plate Count (TPC) parameter. The use of Personal Protective Equipment (PPE) such as mask, gloves, headgear, and apron is important to minimize contamination of microorganism from food handlers to food produced. In addition, the selection of ingredients, storage duration, and storage temperature are required to be considered. Suggestion for the cafeteria supervisor of SDN Model and food handler: for the cafeteria supervisor SDN Model to impose regulation and education for food handlers to use PPE during food processing. It is suggested to food handlers to get used to in using PPE during processing the food